2017
DOI: 10.1136/bmjgh-2017-000496
|View full text |Cite
|
Sign up to set email alerts
|

Vertical and horizontal equity of funding for malaria control: a global multisource funding analysis for 2006–2010

Abstract: BackgroundInternational and domestic funding for malaria is critically important to achieve the Sustainable Development Goals. Its equitable distribution is key in ensuring that the available, scarce, resources are deployed efficiently for improved progress and a sustained response that enables eradication.MethodsWe used concentration curves and concentration indices to assess inequalities in malaria funding by different donors across countries, measuring both horizontal and vertical equity. Horizontal equity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Evidence from previous infectious disease outbreaks, such as malaria, warns that funding during emergencies tend to be provided in line with health and economic need, but biassed towards richer areas. 54 In light of the correlation between CCG-level vulnerability and deprivation reported in this paper, the distribution of resources in times of emergencies should be guided by communitylevel factors. Guidelines for 'fair allocation of resources' should be developed based on direct knowledge about local communities-not only considering the health impact of such choices, but also long-run economic and social impacts for the community.…”
Section: Discussionmentioning
confidence: 91%
“…Evidence from previous infectious disease outbreaks, such as malaria, warns that funding during emergencies tend to be provided in line with health and economic need, but biassed towards richer areas. 54 In light of the correlation between CCG-level vulnerability and deprivation reported in this paper, the distribution of resources in times of emergencies should be guided by communitylevel factors. Guidelines for 'fair allocation of resources' should be developed based on direct knowledge about local communities-not only considering the health impact of such choices, but also long-run economic and social impacts for the community.…”
Section: Discussionmentioning
confidence: 91%
“…An initial focus on high-and moderatetransmission settings is further supported by our results showing that a balance can be found between achieving close to optimal case reductions while also progressing towards elimination in the maximum number of settings. Even within a single country, targeting interventions to local hot-spots has been shown to lead to higher cost savings than universal application, [28] and could lead to elimination in settings where untargeted interventions would have little impact. [25] Assessing optimal funding patterns is a global priority due to the funding gap between supply and demand for resources for malaria control and elimination.…”
Section: Discussionmentioning
confidence: 99%
“…This illustrates the possibility that such an allocation approach can potentially target certain countries disproportionally and result in further inequities in health outcomes. [28] From an international funder perspective, achieving vertical equity might therefore also encompass higher disbursements to countries with lower affordability of malaria interventions, [28] as reflected in the Global Fund's proportional allocation formula which accounts for the economic capacity of countries. [14] While our models are based on country patterns of transmission settings and corresponding populations in 2000, there are several factors leading to heterogeneity in transmission dynamics at the national and sub-national level which were not modelled and limit our conclusions.…”
Section: Different Priorities In Resource Allocation Decisions Greatl...mentioning
confidence: 99%
“…It is crucial that the use of funds responds to the real needs of a country. A study by Barrenho demonstrated the importance of effective coordination among different donors of malaria funds if a good level of performance in relevant policies is to be achieved [37].…”
Section: Fundingmentioning
confidence: 99%